2011
DOI: 10.2174/1745017901107010117
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Effectiveness of a Telephone-Based Nursing Strategy for Enhancing Medication Adherence in Schizophrenia

Abstract: A post hoc analysis was made to identify factors associated with success following a 4-month telephone-based strategy for enhancing adherence to antipsychotic treatment in schizophrenia. A total of 928 stable outpatients were randomized to receive a monthly telephone call provided by a nurse or routine clinical care. Logistic regression with a backward stepwise procedure was used. A higher percentage of patients in the intervention group (25.7%, n=109) improved adherence at the end of the study compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…A key finding of this review was that mobile phone contacts (text messaging/phone calls) have been used to promote medication adherence in individuals with SMI, and the studies reviewed showed that mobile phone contacts, especially text messages, were effective in reminding study participants to take their medications (Beebe et al, 2008; Beebe et al, 2014; Granholm et al, 2012; Montes et al, 2010; Montes et al, 2012). These results were noted in similar studies (Kunigiri, Gajebasia, & Sallah, 2014; Montes, Maurino, Diez, & Saiz-Ruiz, 2011; Van Gent & Knoppert Van Der Klein, 2010). Moreover, for all the studies reviewed, the use of mobile phone contacts achieved higher medication adherence rates across all the studies.…”
Section: Discussionsupporting
confidence: 80%
“…A key finding of this review was that mobile phone contacts (text messaging/phone calls) have been used to promote medication adherence in individuals with SMI, and the studies reviewed showed that mobile phone contacts, especially text messages, were effective in reminding study participants to take their medications (Beebe et al, 2008; Beebe et al, 2014; Granholm et al, 2012; Montes et al, 2010; Montes et al, 2012). These results were noted in similar studies (Kunigiri, Gajebasia, & Sallah, 2014; Montes, Maurino, Diez, & Saiz-Ruiz, 2011; Van Gent & Knoppert Van Der Klein, 2010). Moreover, for all the studies reviewed, the use of mobile phone contacts achieved higher medication adherence rates across all the studies.…”
Section: Discussionsupporting
confidence: 80%
“…By far, the most commonly collected data were basic psychiatric symptom assessments (A.9.1), for example, early warning signs of psychosis [ 105 ], illicit drug cravings [ 115 ], withdrawal symptoms [ 70 , 90 ], mood [ 107 , 116 ], or PTSD symptoms [ 112 ]. Other studies tracked attitudes toward medication [ 117 ] or medication side effects [ 118 , 119 ] to guide motivational interventions (A.9.2). Others tracked potential triggers or indices for relapse likelihood including stress, anxiety, sleep, and social support [ 42 , 44 , 120 ].…”
Section: Resultsmentioning
confidence: 99%
“…Adherence to antipsychotic treatment was estimated by the treating psychiatrist and the nurse according to the Register of Adherence to Treatment scale (RAT): high (adherence with 80% of doses), moderate (adherence with 60-79% of doses), low (adherence with 20-59% of doses), and nil (adherence with < 20% of doses). In summary, the results of this study detect that a telephone call made by a mental health nurse is a successful intervention for enhancing adherence in stable patients with schizophrenia, especially useful for improving adherence in those patients with a negative attitude towards antipsychotic treatment (Montes et al, 2011).…”
Section: The Corroborative Evidencesmentioning
confidence: 73%